Inverter with Integrated Energy Buffer for Grid Power Management in DWPT Charging - Conceptual Analysis, Design, and Control - Majeed, Hatif Bin Abdul; Pratik, Ujjwal; Abdelraziq, Muhammad; Azad, Ahmed; Pantic, Zeljko (IEEE transactions on transportation electrification, 2025)
Dynamic Wireless Power Transfer (DWPT) inherently results in intermittent power exchange between a moving vehicle and the electric grid. The intermittent power flow subjects the grid to significant stress, potentially affecting grid stability. This study proposes a distinctive transmitter structure and control method to smooth the power pulsation from the grid to the vehicle, downsizing the grid-side power electronics and cable ratings. An energy buffering unit is designed and connected to the DWPT inverter. An advanced inverter control strategy is proposed to regulate the inverter's input and transmitter coil currents simultaneously. The proposed solution solely utilizes the existing inverter; no additional conversion unit is needed. A comprehensive analysis of the system operation is presented, including the derivation of expressions for sizing the energy buffer components and defining the operational boundaries for the inverter's dual-purpose control. In this work, a 22-kW control hardware-in-the-loop (CHIL) setup and a 750-W benchtop scaled-down DWPT hardware prototype are developed for testing. The proposed structure and controls are systematically validated through experiments and real-time simulations. The energy buffering operation is demonstrated, achieving a 75% reduction in power pulsation on the grid side for vehicle speeds up to 75 mph.